Effect of different mini‐volume colloid centrifugation configurations on flow cytometrically sorted sperm recovery efficiency and quality using a computer‐assisted semen analyzer - Ferre, Luis Bernardo (2018)
Straws of sex‐sorted sperm are usually packaged at a low concentration (e.g., ~2.1 × 106 sperm/ml) and cost significantly more than unsorted conventional semen from the same sire. In order to maximize the efficiency of using sex‐sorted sperm under in vitro fertilization conditions, the selection of an appropriate sperm separation technique is essential. In this study, the effect of using different silane‐coated silica colloid dilutions and layering configurations during centrifugation of sex‐sorted sperm was examined over an extended period of incubation time. Sperm recovery and viability after centrifugation using the colloid separation technique were measured along with several sperm motility parameters using CASA. For this purpose, frozen and thawed sex‐sorted sperm samples were centrifuged using mini‐volume single‐layer (40%, 60% and 80%) and mini‐volume two‐layer (45%/90%, 40%/80% and 30%/60%) separation configurations using PureSperm®. A single layer of 40% PureSperm® recovered significantly more sex‐sorted sperm (78.07% ± 2.28%) followed by a single layer of 80% PureSperm® (68.43% ± 2.33%). The lowest sperm recovery was obtained using a two‐layer PureSperm® dilution of 45%/90% (47.57% ± 2.33%). Single‐layer centrifugation recovered more sorted sperm (68.67% ± 1.74%) than two layer (53.74% ± 1.74%) (p < .0001). A single layer of 80% PureSperm® exhibited the highest sorted sperm viability (72.01% ± 2.90%) after centrifugation (p < .05). The mini‐volume single layer of 80% PureSperm® was determined to be an effective alternative to a two‐layer centrifugation configuration for sex‐sorted sperm selection. In addition, single‐layer colloid dilution of 80% performed either as well as or significantly outperformed the other treatments, as well as the control, with regard to motility (MOT) for all time periods of analysis.